Analisis Pengaruh Penempatan Balok Anak pada Perencanaan Pelat Lantai Gedung Toko Satu Sama - Karel Agung; Jonie Tanijaya; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2021)
One model of structural planning that can be used to make the building structure efficient is to add the secondary beams. Based on these assumptions, this paper is made to analyze the effect of placing secondary beams on the floor structure of the building to determine the efficiency that occurs to the thickness of the slab and the reinforced concrete material used. In the case of planning the Toko Satu Sama building on Jl. Perintis Kemerdekaan City Makassar floor plan is given one secondary beam on the x-direction and produces a plate thickness of 150 mm. The floor plan is re-planned by making a floor plan without secondary beams, a floor plan with y-directional secondary beams and a floor plan with x-and-y secondary beams. The bending moment that occurs on the floor plate is calculated using the 1971 PBI method, but still considering the latest provisions in SNI 2847, 2019. The results of the calculation showed that the floor plan with the pattern of placement of secondary beams in the direction of x and y (h = 120 mm) can streamline the plate by 20% of the thickness of the plate with the pattern of placement of the secondary beam in the direction of x. In line with that, concrete needs can be effective by 15,359 % (12,284 m3). Even if it has more reinforcement needs, the pattern of placement of secondary beams in the direction of x and y is the most efficient pattern.English translation.